Gender equality and government policy as predictors of career choice among Women Civil Servants at Ministry of Natural Resources and Environment, Putrajaya / Atikah Musa... [et al.] - Musa, Atikah; Abdul Razak, Nur Syafeeqa Maulad; Haris, Siti Melinda; Ab.Rahman, Farah Adilla (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Women’s credibility to be in an employment sector is always being underestimated by men. While seeming the progress towards the empowerment of women in the public sector, yet they are still constrained in many ways. The aim of this study is to analyse the factors influencing career choice among women in public sector particularly at the Ministry of Natural Resources & Environment (NRE), Putrajaya. The study examined two factors which are gender equality and government policy in women employment. Survey questionnaires were used to gather information from 160 women civil servants at Ministry of Natural Resources & Environment (NRE), Putrajaya. This study employed quantitative method to identify the correlation of the variables. Findings revealed that gender equality and government policy have significant relationship with their career choice in the public sector.